A Narative Review: The Difference of Satisfaction Level in BPJS Patient And General Patient Toward The Quality of Health Service In Inpatient’s Unit - Sumadi, Andrias Feri; Hidayat, Muhammad Syamsu; Sulistyawati, Sulistyawati (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2021)
Background: Many studies show that the quality of services at various health facilities is influenced by the source of financing. The same thing was also found in the Inpatient Unit. Various data show that there are differences in patient care between general patients and BPJS patients. This is of course contrary to the Presidential Regulation of the Republic of Indonesia No.82 of 2018 that BPJS participants are entitled to health services according to the medical needs required. Therefore, this study aims to discuss how much difference the level of satisfaction of BPJS patients and general patients with the quality of service in the Inpatient Unit. Subject and Methodology: The study method was carried out with a Narative review approach sourced from the PubMed, Google Schollar and IJPHS databases. There are 39,970 articles found with the keywords patient satisfaction and quality of health services; patient satisfaction and quality of health services. Then the articles were identified, filtered, so that 5 articles that met the criteria were obtained for in-depth review. Results: Broadly speaking, there are differences in the satisfaction level of BPJS patients and general patients with the quality of service in the Inpatient Unit. The difference lies in satisfaction in the dimensions of reliability / tangible, responsiveness / responsiveness, assurance, caring / empathy, and direct evidence / reliability. Conclusion: As many as 60% of studies show that there is a difference in the level of satisfaction between BPJS patients and general patients in the Inpatient Unit which can be used as an evaluation for Health Service Providers so that there is no difference in patient satisfaction levels. This is because every patient is unable to get the same health services according to their medical needs. Latar Belakang: Banyak penelitian yang menunjukan bahwa kualitas layanan pada berbagai fasilitas kesehatan dipengaruhi oleh sumber pembiayaan. Hal serupa juga ditemukan di Unit Rawat Inap. Berbagai data menunjukan bahwa ada perbedaan layanan pasien antara pasien umum dan pasien BPJS. Hal ini tentunya bertentangan dengan Peraturan Presiden Republik Indonesia No.82 Tahun 2018 bahwa peserta BPJS berhak mendapatkan layanan kesehatan sesuai dengan kebutuhan medis yang diperlukan. Oleh karena itu, penelitian ini bertujuan untuk membahas seberapa besar perbedaan tingkat kepuasan pasien BPJS dan pasien umum terhadap mutu pelayanan di Unit Rawat Inap. Subjek dan Metodologi: Metode studi dilakukan dengan pendekatan Narative review yang bersumber pada database PubMed, Google schollar dan IJPHS. Terdapat 39.970 artikel yang ditemukan dengan kata kunci kepuasan pasien dan mutu layanan kesehatan; patient satisfaction and quality of health services. Selanjutnya artikel tersebut diidentifikasi, disaring, hingga diperoleh 5 artikel yang memenuhi kriteria untuk kemudian diulas secara mendalam. Hasil:  Secara garis besar terdapat perbedaan tingkat kepuasan pasien BPJS dan pasien umum terhadap mutu pelayanan di Unit Rawat Inap. Perbedaan terletak pada kepuasan pada dimensi kehandalan/tangible, daya tanggap/ responsiveness, jaminan/assurance, peduli/empaty, dan bukti langsung/ reliability. Kesimpulan: Sebanyak 60% penelitian menunjukan adanya perbedaan dalam tingkat kepuasan antara pasien BPJS dan pasien umum di Unit Rawat Inap dapat dijadikan evaluasi bagi Pelaksana Layanan Kesehatan sehingga tidak ada lagi perbedaan tingkat kepuasan pasien. Hal ini dikarenakan setiap pasien berhak mendapatkan layanan kesehatan yang sama sesuai dengan kebutuhan medisnya.